2011
DOI: 10.1186/1471-2172-12-56
|View full text |Cite
|
Sign up to set email alerts
|

RAGE and ICAM-1 differentially control leukocyte recruitment during acute inflammation in a stimulus-dependent manner

Abstract: BackgroundThe receptor for advanced glycation endproducts, RAGE, is involved in the pathogenesis of many inflammatory conditions, which is mostly related to its strong activation of NF-κB but also due to its function as ligand for the β2-integrin Mac-1. To further dissect the stimulus-dependent role of RAGE on leukocyte recruitment during inflammation, we investigated β2-integrin-dependent leukocyte adhesion in RAGE-/- and Icam1-/- mice in different cremaster muscle models of inflammation using intravital micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 30 publications
(44 reference statements)
6
37
0
1
Order By: Relevance
“…In line with previous reports [31, 32] we found comparable baseline leukocyte adhesion in cremaster muscle venules of WT, LFA1-KO, and ICAM1-KO mice. In contrast to WT mice, injection of 0.5 g/kg glucose in ICAM1 −/− and in LFA1 −/− mice did not lead to significant changes of adherent leukocytes compared to baseline values (Figure 1(a)).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous reports [31, 32] we found comparable baseline leukocyte adhesion in cremaster muscle venules of WT, LFA1-KO, and ICAM1-KO mice. In contrast to WT mice, injection of 0.5 g/kg glucose in ICAM1 −/− and in LFA1 −/− mice did not lead to significant changes of adherent leukocytes compared to baseline values (Figure 1(a)).…”
Section: Resultssupporting
confidence: 93%
“…We and others demonstrated that injection of CXCR2-binding chemokine CXCL1 induces a significant increase of leukocyte adhesion which is mostly attributed to LFA1 activation and its subsequent ICAM1 binding [23, 31]. …”
Section: Resultsmentioning
confidence: 99%
“…RAGE activation, however, is thought to induce NF-κB nuclear translocation and amplification of downstream signaling pathways (65, 66), including a number of which promote expression of adhesion molecules such as VCAM-1 (67) and ICAM-1 (68). Two studies exploring the relationship between RAGE and ICAM-1 expression on endothelial cells demonstrated complementary roles for ICAM-1 and RAGE in mediating leukocyte adhesion to endothelium (69, 70). It is thus possible that RAGE mediates ILC2 accumulation not directly, but by regulating other downstream mediators such as vascular adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model of acute peritonitis and subsequent in vitro studies, RAGE was shown to directly bind and recruit leukocytes via interactions with Mac-1 on the white blood cell surface [47]. In a follow-up study, endothelial RAGE was found to bind Mac-1 in conjunction with intercellular adhesion molecule 1 (ICAM-1) to recruit leukocytes into the tissue [62,63]. RAGE was also crucial for leukocyte adhesion in studies using blood cells from preterm infants, suggesting a role for RAGE in young, developing animals that have high receptor expression [64].…”
Section: Introduction To Rage Biologymentioning
confidence: 99%